Machine drawing - Lakshminarayana, Kodali, 1908- (New Age International Ltd., 2006)
About the Book: Written by three distinguished authors with ample academic and teaching experience, this textbook, meant for diploma and degree students of Mechanical Engineering as well as those preparing for AMIE examination, incorporates the latest standards. The new edition includes the features of assembly drawings, part drawings and computer-aided drawings to cater to the needs of students pursuing various courses. The text of the new edition has been thoroughly revised to include new concepts and practices in the subject. It should prove an ideal textbook. Contents: Introduction.